Factors that influence abandoned housing project: An IPMA analysis on the Malaysian construction industry - Khairul Aiman, Zainal Abidin; Muhammad Fakhrul, Yusuf (Universiti Teknologi MARA, Perlis Branch, 2019)
Abandoned construction is one of the problems that faced by company and organization that involved in a construction project. This issue has badly affected the development in the cities and may cause social and community problems. This is a concern that may hinder the steps to achieve sustainable development goals. Thus, this research objective is to study the factor that influences the abandoned housing project in Malaysia. Quantitative method is used in this study where 63 respondents were involved in this survey. The Important Performance Map Analysis (IPMA) was used to analyse the data. This analysis is crucial to identify the critical factors that contribute to an abandoned housing project. The result showed that the financial factor and project controlling and monitoring was the critical factor causing abandoned housing project while the contract and procurement, sourcing and design, and external factor have a lower effect. The findings of this research contribute valuable knowledge and solutions to the developer and policy maker, hence enable them to make informed decisions to avoid future incomplete housing project.